2016
DOI: 10.1080/02786826.2016.1163320
|View full text |Cite
|
Sign up to set email alerts
|

Volatility characterization of nanoparticles from single and dual-fuel low temperature combustion in compression ignition engines

Abstract: This work explores the volatility of particles produced from two diesel low temperature combustion (LTC) modes proposed for high-efficiency compression ignition engines. It also explores mechanisms of particulate formation and growth upon dilution in the near-tailpipe environment. The number distribution of exhaust particles from low-and mid-load dual-fuel reactivity controlled compression ignition (RCCI) and single-fuel premixed charge compression ignition (PPCI) modes were experimentally studied over a gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
(38 reference statements)
3
11
0
Order By: Relevance
“…Homogeneous nucleation of hydrocarbons occurs at much higher concentrations than required for sulfuric acid. Similar work in a low temperature combustion system concluded hydrocarbon concentrations were too low for homogeneous nucleation and suggested that unknown, very low volatility species are responsibility for nucleation (Lucachick et al 2016). This is consistent with other findings that other low volatility hydrocarbons, not found in lubricating oil but potentially formed when subjected to high temperature cylinder conditions, such as organic acids, impact nucleation (Arnold et al 2012).…”
Section: ½2supporting
confidence: 86%
“…Homogeneous nucleation of hydrocarbons occurs at much higher concentrations than required for sulfuric acid. Similar work in a low temperature combustion system concluded hydrocarbon concentrations were too low for homogeneous nucleation and suggested that unknown, very low volatility species are responsibility for nucleation (Lucachick et al 2016). This is consistent with other findings that other low volatility hydrocarbons, not found in lubricating oil but potentially formed when subjected to high temperature cylinder conditions, such as organic acids, impact nucleation (Arnold et al 2012).…”
Section: ½2supporting
confidence: 86%
“…Prikhodko et al [33] found that RCCI was highly dominated by nucleation mode particles. Several studies confirm that RCCI produces lower number of particles amongst other LTC strategies [34] [35]. Kolodziej et al [36] also studied the effects of the diesel proportion and the injection timings in the particle size while operating under RCCI.…”
Section: Introductionmentioning
confidence: 99%
“…However, a slight increase in accumulation-mode particles was observed while the nucleation-mode particles decreased, approximately in the same proportion, with the SoE2 advance. As previously analyzed, the SoE2 advance reduces the mixing time, facilitating the carbonaceous particles formation (accumulation-mode) and consequently provides a large surface area for adsorption of the volatile condensates, 49,50 decreasing the concentration of nucleationmode particles.…”
Section: Influence Of Ipmentioning
confidence: 85%
“…In this case, the nucleation mode is promoted against the accumulation mode due to the low absorption of volatiles that can take place on the surface of the carbonaceous particle under these conditions. 49,50 The changes in the accumulation mode can be observed in the particle mass scale, as the PN is so low that the variation cannot be clearly observed in the number scale. In the nucleation mode, a slight increase in PN emissions was observed with the decrease in IP, without significant shifts of the PSDs to larger sizes.…”
Section: Influence Of Ipmentioning
confidence: 99%